Metode Prototype dalam Pengembangan Website Jasa Pengiriman Barang - Indah Ariyati; Rana Fauziyyah (Journal of Informatic and Information Security, 2022)
The use of the website has led to all fields, every company uses the website as a media liaison between the community and the company. Website is online information that can be accessed anytime and anywhere by connecting to the internet network. PT data management The main mainstay of automotive transportation is still manual, errors often occur when data is exchanged or even lost, resulting in errors in sending and delays in reports. Using the prototype method, the researchers developed a goods delivery service website supported by XAMPP 3.2.2 software, Sublime Text, PHP programming language and MySQL database. PT. Andalan Utama Transportasi Otomotif improves goods delivery services, making it easier for customers to access goods delivery information and delivery status updates.